NOTE ON HYPEROSTOSIS IN THE PERCH POMADASYS HASTA (BLOCH) - Nammalwar, P (Indian Journal of Fisheries, 2011)
A case of hyperostosis in the skull bones of the perch, Pomadasys hasta,is reported. The oval-s.haped protuberance of frontal and supraoccipital bonesof the skull and also a small depression between the eyes are very prominent.This gives to the skull a hump-like appearance